Directed Differentiation of Zebrafish Pluripotent Embryonic Cells to Functional Cardiomyocytes - Yao Xiao (Stem Cell Reports, 2016)
A cardiomyocyte differentiation in vitro system from zebrafish embryos remains to be established. Here, we have determined pluripotency window of zebrafish embryos by analyzing their gene-expression patterns of pluripotency factors together with markers of three germ layers, and have found that zebrafish undergoes a very narrow period of pluripotency maintenance from zygotic genome activation to a brief moment after oblong stage. Based on the pluripotency and a combination of appropriate conditions, we established a rapid and efficient method for cardiomyocyte generation in vitro from primary embryonic cells. The induced cardiomyocytes differentiated into functional and specific cardiomyocyte subtypes. Notably, these in vitro generated cardiomyocytes exhibited typical contractile kinetics and electrophysiological features. The system provides a new paradigm of cardiomyocyte differentiation from primary embryonic cells in zebrafish. The technology provides a new platform for the study of heart development and regeneration, in addition to drug discovery, disease modeling, and assessment of cardiotoxic agents.